POLA PEMBINAAN KAMPUNG BINAAN KELUARGA SAKINAH (KBKS) DI KAMPUNG TASIK SEMINAI KECAMATAN KOTO GASIB TAHUN 2019 - Apsari, Tri; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Sakinah Family Assistance Village (KBKS) in Siak Regency has been started in 2012 in the experimental phase. In 2016, the Siak Regency Government made regulations regarding the Sakinah Family Assisted Village which is regulated in Regent Regulation Number 14 of 2016 concerning Technical Guidelines for the Development Pattern of Sakinah Family Assisted Village in Siak Regency and Regent Regulation Number 16 of 2016 concerning Guidelines for Implementation of Sakinah Family Assisted Village Activities. in Siak Regency which explains that there are 6 patterns of guidance which are an effort of the Siak Regency Government to carry out guidance to the community in order to improve the quality of religious practice and family economic welfare. Tasik Seminai Village is one of the expansion villages in Siak Regency which carried out the Sakinah Family Assisted Village in 2019, where there had been a pilot village that carried out this guidance before, the development of the Sakinah Family Assisted Village in this village should run according to what the government has ordered. plan.The purpose of this study is to describe the pattern of fostering the Sakinah Family Assisted Village (KBKS) in Tasik Seminai Village, Koto Gasib District in 2019.The theoretical concept used is the theory of coaching by Santoso. This type of research is descriptive qualitative. Data collection techniques were carried out by interview and documentation.The results of this study are the pattern of fostering the Sakinah Family Assisted Village (KBKS) in Tasik Seminai Village, Koto Gasib District in 2019 is not optimal. The guidance carried out in Tasik Seminai Village is not in accordance with the regulations set by the government, the guidance only focuses on religious activities and ignores economic development. Keywords: Pattern, Sakinah Family Assisted Village, Coaching